"Weighing Cam": A New Mobile Application for Weight Estimation in Pediatric Resuscitation. (3rd May 2020) - Park, Joong Wan; Kwon, Hyuksool; Jung, Jae Yun; Choi, Yoo Jin; Lee, Ji Soo; Cho, Woo Sang; Lee, Jung Chan; Kim, Hee Chan; Lee, Se Uk; Kwak, Young Ho; Kim, Do Kyun
Abstract: Objective: We evaluated the validity of a newly developed mobile application (i.e. the Weighing Cam) for pediatric weight estimation compared with that of the Broselow tape. Methods: We developed an application that estimates the weight of pediatric patients using a smartphone camera and displays the drug dosage, device size, and defibrillation energy on the screen of the smartphone. We enrolled a convenience sample of pediatric patients aged <16 years who presented at two pediatric emergency departments of two tertiary academic hospitals in South Korea. The pediatric patients' heights and weights were measured; then, one researcher estimated the weights using the application. Using the measured height, we determined the weight estimated by the Broselow tape. We compared the estimated measurements by determining the mean percentage error (MPE), mean absolute percentage error, root mean square percentage error, and percentages predicted within 10% and 20% of the actual. Results: In total, 480 patients were enrolled in 16 age categories, each with 15 males and 15 females of different ages. The Weighing Cam demonstrated a lower bias (mean difference: −1.98% [95% confidence interval −2.91% to −1.05%] for MPE) and a higher proportion of estimated weights within 10% of the actual weights than the Broselow tape (mean difference: 9.1% [95% confidence interval 3.0% to 15.1%]). The Weighing Cam showed better performance in terms of accuracy and precision than the Broselow tape in all subgroups stratified by age or body mass index percentile. Conclusions: The Weighing Cam may estimate pediatric patients' weights more accurately than the Broselow tape. The Weighing Cam may be useful for pediatric resuscitation in both prehospital and hospital settings.